2019
DOI: 10.15171/ijep.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Erythromycin Resistance in Methicillin-Resistant Staphylococcus aureus Isolated From Raw Milk

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) strains are one of the most important multidrug resistant microorganisms that threaten human health. Objective: The present study was conducted to evaluate genotypic and phenotypic characteristics of erythromycin resistance among MRSA isolates recovered from raw milk in Iran. Materials and Methods: A total of 50 MRSA isolates were recovered from raw milk. Tests for erythromycin and clindamycin susceptibility and inducible clindamycin resistance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
0
0
1
Order By: Relevance
“…In this study, the antimicrobial susceptibility profiles of S. aureus were determined and high levels of resistance to erythromycin (52.1%) followed by clindamycin (42.8%) were detected. This resistance rate is comparable to one found by another study Mahdavi and colleagues in which they reported 48% and 46% resistance to erythromycin and clindamycin [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the antimicrobial susceptibility profiles of S. aureus were determined and high levels of resistance to erythromycin (52.1%) followed by clindamycin (42.8%) were detected. This resistance rate is comparable to one found by another study Mahdavi and colleagues in which they reported 48% and 46% resistance to erythromycin and clindamycin [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…У цьому контексті антибіотикостійкі бактерії у тварин, яких використовують для одержання харчових продуктів, являють собою серйозну загрозу як потенційне джерело інфекцій людини (Horiuk, 2018;Abreu et al, 2019;Medina et al, 2020). Такий зооноз може відбуватися як через прямий контакт з тваринами, так і у процесі виробництва і споживання продуктів тваринного походження (Kukhtyn et al, 2017;Mahdavi et al, 2019;Rahi et al, 2020). Стурбованість викликає не тільки потенційна передача самих резистентних мікроорганізмів, але і горизонтальна передача генів детермінант стійкості від мікрофлори тварини до патогенів людини Alnakip et al, 2019).…”
Section: вступunclassified